Identification of a 5-[3-phenyl-(2-cyclic-ether)-methylether]-4-aminopyrrolo[2, 3-d]pyrimidine series of IGF-1R inhibitors. Issue 8 (15th April 2016) - Stauffer, Frédéric; Cowan-Jacob, Sandra W.; Scheufler, Clemens; Furet, Pascal
Graphical abstract: Abstract: We report structure-guided modifications of the benzyloxy substituent of the Insulin-like Growth Factor-1 Receptor (IGF-1R) inhibitor NVP-AEW541. This chemical group has been shown to confer selectivity against other protein kinases but at the expense of a metabolism liability. X-ray crystallography has revealed that the benzyloxy moiety interacts with a lysine cation of the IGF-1R kinase domain via its ether function and its aromatic π-system and is nicely embedded in an induced hydrophobic pocket. We show that 1, 4-diethers displaying an adequate hydrophobic and constrained shape are advantageous benzyloxy replacements. A single digit nanomolar inhibitor (compound20, IC50 = 8.9 nM) was identified following this approach.